2021
DOI: 10.1364/ol.415257
|View full text |Cite
|
Sign up to set email alerts
|

Experimental demonstration of second-harmonic generation in high χ2 metasurfaces

Abstract: Metasurfaces able to concentrate light at various wavelengths are promising for enhancing nonlinear interactions. In this Letter, we experimentally demonstrate infrared second-harmonic generation (SHG) by a multi-resonant nanostructure. A 100 GaAs layer embedded in a metal-insulator-metal waveguide is shown to support various localized resonances. One resonance enhances the nonlinear polarization due to the transverse magnetic (TM)-polarized pump wavelength near 3.2 µ m … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 27 publications
0
1
0
Order By: Relevance
“…Even beyond the linear regime, plasmonic metasurfaces provide a versatile way to shape light [18]. The conversion process can be further improved by utilizing multiple-resonant nanoparticles, where the LSPR enhancement occurs simultaneously at the pump and signal wavelengths [19][20][21][22]. Recently, the relevance of double-resonance in the presence of SLRs along orthogonal directions has been stressed out theoretically [23] and was experimentally demonstrated [24].…”
Section: Introductionmentioning
confidence: 99%
“…Even beyond the linear regime, plasmonic metasurfaces provide a versatile way to shape light [18]. The conversion process can be further improved by utilizing multiple-resonant nanoparticles, where the LSPR enhancement occurs simultaneously at the pump and signal wavelengths [19][20][21][22]. Recently, the relevance of double-resonance in the presence of SLRs along orthogonal directions has been stressed out theoretically [23] and was experimentally demonstrated [24].…”
Section: Introductionmentioning
confidence: 99%
“…SHG can further be enhanced by utilizing doubleresonant mechanisms, where the resonance enhancement occurs at both the fundamental and harmonic wavelengths. [24][25][26][27][28][29][30] Having a resonance at the emission signal is also beneficial when amplifying other nonlinear optical processes such as difference frequency generation for efficient terahertz sources, 31 which is called Purcell effect. Note that the SHG response cannot be simply explained by the resonance effects, since the directions of plasmon oscillations supported by the particle geometry and associated local-field distributions also play crucial roles, as confirmed by Czaplicki et al 32 Different from the previously reported work, this study is anchored in a dual resonance model involving Fano and SLR (namely, considering two high-Q resonance mechanisms simultaneously) for the first time, with the aim of investigating the coupling between distinct resonance modes in the context of enhancing optical SHG.…”
Section: -Fold Enhancement Of Second-harmonic Generation By Coupled D...mentioning
confidence: 99%